Danzica e le guerre wikipediane. Qualche osservazione sulle edit wars - Jacopo Bassi (Diacronie. Studi di Storia Contemporanea, 2017)
What kind of relationship do the historical sciences have with Wikipedia? How should a reader approach Wikipedia articles dealing with history? What role will the upcoming “free encyclopedia” play in the study and teaching of history? Starting from an analysis on some Wikipedia’s article performed by the “Nicoletta Bourbaki” working group, six authors animate a panel discussion on the relationship between the free encyclopedia and history.